Development of Reservoir Rehabilitation and it Impact on the Surrounding Community (Study of Penjalin Reservoir, Paguyangan District, Brebes Regency, 2017-2022): Perkembangan Rehabilitasi Waduk dan Dampaknya terhadap Masyarakat Sekitar (Studi Waduk Penjalin Kecamatan Paguyangan Kabupaten Brebes tahun 2017-2022) - Roni, Roni Mustofa (Mitreka Satata: Journal of Historical Studies and History Education, 2026)
Penjalin Reservoir is one of the legacies of the Dutch colonial government located in Winduaji village. In its historical development, rehabilitation was carried out in 2018. So this study is interested in discussing the problems in this study are: first, how is the history of Penjalin Reservoir in Paguyangan in 1930. Second, what are the functions of Penjalin Reservoir for the lives of the people around Paguyangan District from 2017-2022. Third, what are the impacts of rehabilitation on the socio-economic conditions of the Penjalin Reservoir community in 2018-2021. This study aims to describe the history of Penjalin Reservoir, find out the function of Penjalin Reservoir and analyze the impact of Penjalin Reservoir rehabilitation. The research method used in this study is a historical research method consisting of four stages, namely 1. Heuristics (the stage of searching and collecting data), 2. Verification in this stage is divided into two, namely external criticism (source authentication) and internal criticism (credibility of historical sources), 3. Interpretation, namely interpreting and arranging 4. Historiography, namely the stage of writing history The results of this study prove that the Penjalin Reservoir is one of the building heritages of the Dutch colonial period, this reservoir is not only used for irrigation but is also used in many sectors, especially tourism with the construction of the Penjalin Reservoir tower which is a characteristic of tourism in the Penjalin Reservoir, rehabilitation carried out in 2018 experienced several improvements, namely on the body of the Dam et al.